60.8k views
2 votes
May you simply explain this concept I've been lost on this all day.

May you simply explain this concept I've been lost on this all day.-example-1
User AQuirky
by
6.3k points

1 Answer

0 votes

Answer:


(x+(5)/(2))^2-(1)/(4)

Step-by-step explanation:

Given a quadratic equation of the form:


y=ax^2+bx+c

To "complete the squares" is to rewrite it as:


y=a(x+d)^2+e

Where:


d=(b)/(2a)
e=c-(b^2)/(4a)

In this case, we are given:


y=x^2+5x+6

Then:

a = 1

b = 5

c = 6

Using the formulas above:


d=(5)/(2\cdot1)=(5)/(2)
e=6-(5^2)/(4\cdot1)=6-(25)/(4)=-(1)/(4)

Now, we can rewrite:


y=(x+(5)/(2))^2-(1)/(4)

User Kaustav Ray
by
6.1k points